Probable multi-year trends of degradation of post-pyrogenic forest soils in Russia - S. A. Avetyan; M. I. Gerasimova; N. V. Savitskaya; T. V. Ananko; I. Yu. Savin; E. A. Shishkonakova (Бюллетень Почвенного института им. В.В. Докучаева, 2025)
A comparison of soil-geographical units of the Unified State Register of Soils of Russia with a database on the disappearance of woody forest vegetation for the period from 2000 to 2021, built on Landsat satellite data, made it possible to identify soil areas in the country that were affected by forest fires. The greatest impact on the soil cover is noted for the Asian part of the Russian Federation within the cryolithozone, where the pyrogenesis zone mainly includes the most common here thin rubble soils of mountain taiga forests: podburs, podzols, rzhavozems, cryohomogeneous peat-cryozems, soils of the organo-accumulative section, (carbo)lithozems, petrozems, i.e. soils most susceptible to erosion processes, as well as ice-frozen fine-earth soils of medium-heavy granulometric composition: pale yellow, pale solodized, gleyzems, cryozems, in which the processes of paludification, cryosolifluction, thermokarst are activated. The probability of activation of post-pyrogenic soil degradation processes as a result of forest loss in the period from 2000 to 2021 exists on approximately 16 % of the territory of Russia. These are water (10 %) and wind (8 %) erosion, paludification (about 15 %) and cryogenic processes of solifluction (10 %) and thermokarst (7 %). Areas with a potential for increased post-fire water erosion are located in the Central Siberian Plateau, Transbaikalia, North-Eastern Yakutia, the south of the Far East; deflation – in Yakutia, northern Baikal and Transbaikalia, paludification – in the Central Yakut lake-alluvial plain, in the intermountain basins of Transbaikalia and North-Eastern Yakutia, in Western Siberia, cryosolifluction and thermokarst – in Central and Northern Yakutia, Krasnoyarsk Krai, Magadan Oblast, and in the north of Amur Oblast.